The Character of Legal Products in Indonesia: A Study of Changes to the Marriage Law from a Political-Law Perspective - Nasrullah, Nasrullah; Andriawan, Wawan; Musawar, Musawar (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2024)
Politics and law are two variables that can influence each other in a legal system. Legal politics is a form of state policy carried out through authorized state institutions to establish the desired regulations, which are expected to be used to express what is contained in society and to achieve the desired goals. This research aims to examine the character of statutory legal products, namely the character of legal products of Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 concerning Marriage. This research is normative legal research which makes norms the object of study using a legal approach analyzed using legal political theory. The data collection technique used is literature study. Research findings show that in general the character of the legal product of Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 concerning Marriage is responsive in view of the birth of the law. However, the provisions of Article 7 paragraph (2) of Law Number 16 of 2019 do not show a responsive or conservative character. The provisions in this article are not in accordance with the spirit of change based on Constitutional Court Decision Number 22/PUU-XV/2017 and seem ahistorical. Theoretically, the conservative character in legal politics is a legal product that is not democratic, different from responsive legal products, namely legal products that accommodate a variety of opinions. Other findings show that there is no judicial institution that has the authority to check the consistency between the provisions of one article or paragraph and another in one form of legal product.